THE EFFECT OF LEADERSHIP STYLE, ORGANIZATIONAL COMMITMENT, AND UNDERSTANDING OF GOOD GOVERNANCE ON GOVERNMENT AUDITOR PERFORMANCE IN BPKP CENTRAL SULAWESI REPRESENTATIVE - Masdar, Rahma; Pattawe, Abdul; Meldawati, Lucyani (LPPM Universitas Tadulako, 2020)
This study aimed to determine and analyze the influence of leadership style, organizational commitment, and understanding of good governance on auditor performance. This study used a purposive sampling method by giving criteria for sampling. Data collection was carried out by distributing questionnaires to BPKP auditors. Primary data were obtained from the responses of respondents through the distribution of questionnaires, observations and interviews. Data were analyzedusing Multiple Linear Regression with the help of IBM SPSS Statistics 25. The results showed that leadership style, organizational commitment, and understanding of good governance simultaneously had a significant effect on auditor performance. Partially, leadership style had a significant effect on auditor performance, organizational commitment had a significant effect on auditor performance, and understanding of good governance had a significant effect on auditor performance.